1994
DOI: 10.1111/j.1439-0442.1994.tb00123.x
|View full text |Cite
|
Sign up to set email alerts
|

Phagocytic Activity of Polymorphonuclear Leukocytes Lavaged from the Lungs of Horses with Clinically Diagnosed Chronic Pulmonary Disease

Abstract: Summary The aim of this study was to compare phagocytic activity of polymorphonuclear cells (PMNs) from the bronchoalveolar lavage of clinically healthy horses and those with severe chronic bronchiolitis. Research was carried out on 28 horses. Chronic inflammation of the lower airways was diagnosed in nine horses. Cells from the respiratory tract were lavaged according to accepted methods. For comparison, PMNs were isolated from peripheral blood of all investigated horses. The phagocytic activity of PMNs was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…Their significant increase is detectable in TA as well as in BALF. The present results confirm previous findings (Beech 1975, Derksen 1989, Kluciński et al 1994. The undisputed fact is that noninfectious inflammation leads to a 10 fold increase in the number of cells in TA and BALF and among these cells, the highest proportion are neutrophils.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Their significant increase is detectable in TA as well as in BALF. The present results confirm previous findings (Beech 1975, Derksen 1989, Kluciński et al 1994. The undisputed fact is that noninfectious inflammation leads to a 10 fold increase in the number of cells in TA and BALF and among these cells, the highest proportion are neutrophils.…”
Section: Discussionsupporting
confidence: 92%
“…The study performed by Kluciński et al (1994) showed that noninfectious inflammation in the airways of RAO affected animals is proceed with changed, by neutrophils presence, mechanism initiating phagocytosis. This study concluded that phagocytosis, initiated by neutrophils, is carried out without immunologically specific receptors, so there is no need for opsonized particles.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The next stage of the procedure was collection of tracheal aspirates and bronchoalveolar lavage fluid in accordance with generally accepted principles (Derksen et al 1989, Kluciński et al 1994, Beech 1975. Tracheal washes where submitted for cytological and microbiological analysis.…”
Section: Endoscopic Exammentioning
confidence: 99%